Multidimensional evaluation of teaching strategies for pharmacology based on a comprehensive analysis involving 21,269 students - Xiao, Chen-Lin; Ren, Huan; Chen, Hui-Qing; Liu, Wen-Hui; Luo, Zhi-Ying; Li, Wen-Ru; Luo, Jian-Quan (Frontiers in Pharmacology, 2023)
Background: Given the limitations of traditional pharmacology pedagogical method, diverse novel teaching methods have been widely explored. In this study, we performed a network meta-analysis (NMA) to evaluate the effects of different strategies in pharmacology teaching. Methods: Literature databases were searched from their inception to November 2022, and the studies were screened according to predefined inclusion and exclusion criteria to extract important information. Outcomes, including theoretical test scores, experimental test scores, subjective test scores, satisfaction scores, and the proportion of satisfaction, were analyzed using R software (version 3.6.1) and STATA (version 15). The NMA was conducted with a random-effects model under the Bayesian framework to calculate odds ratios (ORs) or mean differences (MDs) with associated 95% credible intervals (95% CIs). Surface under the cumulative ranking curve (SUCRA) probability values were calculated to rank the teaching methods examined. Results: A total of 150 studies involving 21,499 students were included. This NMA systematically evaluated 24 teaching strategies, such as problem-based learning (PBL), team-based learning (TBL), case-based learning (CBL) and flipped classrooms (FC), etc. The results of the NMA showed that, PBL combined with CBL was most likely to improve students’ theoretical and subjective test scores (SUCRA = 75.49 and 98.19%, respectively), TBL was most likely to improve the experimental test score (SUCRA = 92.38%) and the satisfaction score (SUCRA = 88.37%), while FC had the highest probability of being the best option for improving the proportion of satisfaction (SUCRA = 84.45%). Conclusion: The current evidence indicates that TBL, PBL combined with CBL, and FC might be optimal strategies for pharmacology teaching since they have a more beneficial effect on students.